Crisis management for people with dementia at home: Mixed‐methods case study research to identify critical factors for successful home treatment. (27th August 2020) - Hopkinson, Jane; King, Amanda; Young, Lucy; McEwan, Kirsten; Elliott, Fiona; Hydon, Kate; Muthukrishnan, Sabarigirivasan; Tope, Rosie; Veitch, Anne‐Marie; Howells, Cristie; Hoskins, Mathew
Abstract: Best practice in dementia care is support in the home. Yet, crisis is common and can often result in hospital admission with adverse consequences. The objective of this mixed‐methods case study research was to identify the critical factors for resolving crisis for a person with dementia living at home. The research was an in‐depth investigation of what happens during crisis for people with dementia and how it is managed by a Home Treatment Crisis Team to resolution and outcome at 6 weeks and 6 months. The methods were; observation of crisis management for 15 patients with dementia (max three observations per patient, total 41), interviews with patients with dementia ( n = 5), carers ( n = 13) and professionals ( n = 14, range one to six interviews per person, total 29), focus group (nine professionals), and extraction of demographics and medical history from medical records. Analysis focused on the identification of factors important for crisis resolution and avoidance of hospital admission. Critical factors for the Home Treatment Crisis Team to enable successful crisis resolution were: immediate action to reduce risk of harm, expertise in dementia care and carer education, communication skills to establish trust and promote benefits of home treatment, shared decision‐making, medication management, addressing the needs of carers independently of the person with dementia and, local availability of respite and other community services. The Home Treatment Crisis Team integrated the seven factors to deploy a biopsychosocial systems approach with embedded respect for personhood. This approach enabled crisis resolution for a person with dementia by creating a system of services, treatments, resources and relationships, 'Safe Dementia Space', in the community with avoidance of hospital admission in more than 80% of referrals. The identified critical factors for crisis resolution are important considerations in the design and delivery of home treatment services for people with dementia.